Studies on Establishment of Transformation System and its Utilization for Breeding in Ruzigrass (Brachiaria Ruziziensis) - Ishigaki, G.; Suenaga, K.; Gondo, T.; Umami, N.; Akashi, R. (2014)
We have established an effective method for plant regeneration system and transformation system mediated particle bombardment in diploid ruzigrass Brachiaria( ruziziensis Germain & Evrard). Additionally, we have attempted to introduceDREB1A gene derived from Arabidopsis thaliana to ruzigrass for production of drought-tolerance transgenic plants. Key Words: Brachiaria, tissue culture, Transformation system, Drought-tolerance